2017
DOI: 10.1121/1.4974858
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic differentiation of Shiho- and Naisa-type short-finned pilot whales in the Pacific Ocean

Abstract: Divergence in acoustic signals used by different populations of marine mammals can be caused by a variety of environmental, hereditary, or social factors, and can indicate isolation between those populations. Two types of genetically and morphologically distinct short-finned pilot whales, called the Naisa-and Shiho-types when first described off Japan, have been identified in the Pacific Ocean. Acoustic differentiation between these types would support their designation as sub-species or species, and improve t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, these whistle characteristics may make it difficult to discern the subtle differences between populations using the time-frequency measurements commonly implemented in whistle classification analyses. Frequency-modulated calls, e.g., whistles, have been categorized into call types to identify geographically isolated populations of some odontocetes based on contour shape and time-frequency characteristics (Saulitis et al, 2005;Van Cise et al, 2017). No attempt was made to categorize whistle types for false killer whales since this study was interested in the overall classification of all whistles.…”
Section: Discussionmentioning
confidence: 99%
“…However, these whistle characteristics may make it difficult to discern the subtle differences between populations using the time-frequency measurements commonly implemented in whistle classification analyses. Frequency-modulated calls, e.g., whistles, have been categorized into call types to identify geographically isolated populations of some odontocetes based on contour shape and time-frequency characteristics (Saulitis et al, 2005;Van Cise et al, 2017). No attempt was made to categorize whistle types for false killer whales since this study was interested in the overall classification of all whistles.…”
Section: Discussionmentioning
confidence: 99%
“…For each of these cases, alternate methods are needed for population sampling. With advances in acoustic methods, researchers have turned to passive acoustic surveys to assess population structures for soniferous species when traditional observational methods or genetic analyses are unavailable or inconclusive (Figure 2) [36,[96][97][98]. Many potential pitfalls in acoustic analyses of population structure parallel those that apply to acoustic species classification.…”
Section: Population Structurementioning
confidence: 99%
“…If the populations being tested are geographically segregated, the location of the recorders can provide this validation if it can be shown that there is enough distance between recorders that sounds from the adjacent population will not be recorded. However, if the populations being tested are sympatric, it is important to use independent means (e.g., visual scans) to identify the focal population or group being recorded and to ensure that individuals from other populations are not present or nearby during the recording (see, for example, [31,98]). In addition to these considerations, the parameters used in the recording and analysis of acoustic data should be consistent across the populations being tested to avoid introducing variability as an artifact of the experimental design.…”
Section: Population Structurementioning
confidence: 99%
“…The vocal repertoire of a wide variety of species has been documented, including birds (Saunders, 1983;Trejos-Araya and Barrantes, 2014), primates (Hammerschmidt and Fischer, 2019;Macedonia, 1993), mustelids (Lemasson et al, 2014;Leuchtenberger et al, 2014;McShane et al, 1995), and marine mammals (Brady et al, 2020;Ford, 1989;Martin et al, 2021;Phillips and Stirling, 2001;Sayigh et al, 2013;Weilgart and Whitehead, 1997). Among marine mammals, studies have shown that vocal repertoire may be integral to the maintenance of population structure (Sharpe et al, 2019;Van Cise et al, 2017;Whitehead et al, 1998;Yurk et al, 2002) and is an important tool for mate attraction (Tyack, 1981). Communication via acoustic signaling is especially important in the marine environment, in which visibility is often limited and animals must rely primarily on sound to navigate their surroundings and communicate with conspecifics (Dudzinski et al, 2009).…”
Section: Introductionmentioning
confidence: 99%